2000
DOI: 10.2307/177220
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of Seedling Establishment: Reduction in Irradiance Enhances Winter Growth of Eucalyptus pauciflora

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
1

Year Published

2001
2001
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 55 publications
(125 reference statements)
2
52
1
Order By: Relevance
“…Certainly, postfire tree seedling regeneration can be suppressed by frost in the first few years after fire (Wimbush and Forrester, 1988). There is no way to confirm our suggested longer-term mechanism here, although there are numerous examples whereby experimental shading of E. paucifiora seedlings in frost-prone areas improves winter survival and growth (e.g., Slatyer, 1976;Ball et al, 1991;Egerton et al, 2000). However, given that some seedlings have established well beyond the influence of protective tree canopies, changes to factors that affect seedling recruitment at local-and regional-scales may also need to be invoked to help explain the more recent success of seedlings.…”
Section: Temperature and Precipitation Records Across The Boundarymentioning
confidence: 72%
“…Certainly, postfire tree seedling regeneration can be suppressed by frost in the first few years after fire (Wimbush and Forrester, 1988). There is no way to confirm our suggested longer-term mechanism here, although there are numerous examples whereby experimental shading of E. paucifiora seedlings in frost-prone areas improves winter survival and growth (e.g., Slatyer, 1976;Ball et al, 1991;Egerton et al, 2000). However, given that some seedlings have established well beyond the influence of protective tree canopies, changes to factors that affect seedling recruitment at local-and regional-scales may also need to be invoked to help explain the more recent success of seedlings.…”
Section: Temperature and Precipitation Records Across The Boundarymentioning
confidence: 72%
“…Egerton et al (2000) found that protected seedlings of Eucalyptus pauciflora at high elevations were less photoinhibited than those in the open. Smith (1999, 2000) found that Abies lasiocarpa and Picea englemanii seedlings were most common in habitats with ;40-80% of the overhead area open to the sky, and demonstrated that seedlings in these habitats benefited from the way in which overstory canopies ameliorated nighttime temperature and lowered light levels.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, other stresses, such as drought and high-temperature stress, as well as wind-blown ice, snow, and dust, can also reduce seedling survival (Tranquillini, 1979;Baskin & Baskin, 1998). Also, PSII responses to freezing temperatures can be complicated by high PFD, which has been shown to affect recruitment in seedlings of other species (Ball et al, 1997;Egerton et al, 2000). Given the broad distribution of A. tridentata across North America, differences among populations in the ability to tolerate freezing would seem likely when compared across larger scales.…”
Section: Discussionmentioning
confidence: 99%